Legal Protection for Sellers in the Use of Joint Accounts as One of the Payments in E-Commerce - Muthia Sakti (Faculty of Law, Universitas Sebelas Maret, 2020)
The development of technology has accompanied the development of a freer and more open means of information. Everyone from all over the world can interact both one way and two ways with various interests. E-Commerce is one of the activities sponsored by technological developments in the era of globalization. One of the payment systems in e-commerce is using a joint account, a payment method for buying and selling goods online using third-party facilities to help create safe and comfortable conditions. In this paper, we will discuss sellers' legal protection in the use of joint accounts in e-commerce. The party that makes a breach of promise of transactions in e-commerce, the seller, one of the parties in the joint account, can legally be protected.